Women's career advancement in organisations: Integrative framework for research - Mišić-Andrić Marijana (Journal of Engineering Management and Competitiveness, 2015)
Contemporary organisations, caught in the middle of global economic and social crisis, are facing different business challenges, having to respond to quick changes in business environment and demographic changes in workforce composed by increasing number of women. Although the number of women in workforce is on the rise, they are still underrepresented in manager positions, especially higher management. This implies that certain barriers are in place which makes difficult for women to develop their careers, especially in reaching manager positions. The aim of this paper is to analyse and present a theoretical framework for further study of professional carrier advancement for women. The paper especially analyse integrative theoretical framework which stresses the equal importance of researching individual factors (personal influence) and organisational factors (social inclusion), having in mind how the organisational context can improve or deter women's carrier. The paper presents possible directions for future research based on the analysis of the theoretical framework and especially individual and organisational factors.